Wabi Sabi in Wabicha Tradition - Rr. Denniza Sekar Adisty; Cuk Yuana (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
The wabicha flow of chanoyu has a lot of simplicity and beauty that is displayed in every procession of the ceremony by changing things that were previously luxurious to be simpler such as chashitsu walls made of wood and thatched roofs, ceremonial utensils made of natural materials, paintings or calligraphy purchased from local merchants, and chabana from local flower gardens. The element of beauty is in the shape, texture, motif or pattern, and atmosphere created in the chanoyu ceremony. The terms in the ceremonial procession show that the host and guests must respect each other. The use of materials by utilizing natural resources creates a simple, harmonious, calm and peaceful atmosphere. This research aims to explain how the representation of wabicha flow in the chanoyu tradition, how the ceremonial procession in the wabicha flow, and the elements of wabi sabi in the wabicha flow. The research method used is descriptive qualitative. While the research approach is a document study approach.